Theory of Emotions in the 18th Century: On the Entanglement of Rationalism, Empiricism, and Aesthetics (KULT_online, 2012)
Ernst Stöckmann's monograph Anthropologische Ästhetik. Philosophie, Psychologie und ästhetische Theorie der Emotionen im Diskurs der Aufklärung (Anthropological Aesthetics: Philosophy, Psychology and the Aesthetic Theory of Emotions in the Discourse of the Enlightenment) offers a complex analysis of the theory of emotions in the 18th century. At the same time, the study writes the story of an ongoing dissolution of Aesthetics from its rationalist origin (Leibniz, Wolff) to its anthropological and psychological formulation. Binding together these research foci makes for the charm and high quality of the examination.